FINANCIAL MARKET AS A BASIS FOR EVALUATING TRANSFORMATION PROCESSES AND FORECASTING ITS EFFICIENCY THROUGH PERFORMANCE: CLASSIFICATION AND FORMS - MYKHALCHYNETS, Halyna (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The financial market model should be formed taking into account a clearly defined subject area and its objects, which is ensured by their classification and adequate representation in form. The described processes are significant since the type and forms of expression of the financial market form the basis for launching evaluation methods and forecasting its effectiveness through performance. The financial market classification consists of supplementing its model with the location and organization of its interrelated elements. It should be noted that for this purpose, systems for dividing objects into groups according to predetermined characteristics should be applied, in particular: 1) division of the financial market according to information about it (into groups, subgroups according to a particular characteristic); 2) allocation of logical connections between groups and subgroups of the financial market. These object distribution systems are based on the identification/construction of structures forming a combinatorial financial market model. The purpose of the article is the process of research the classification and forms of presentation of the financial market as a basis for evaluating transformational processes and forecasting their effectiveness through effectiveness. The process of researching the classification and forms of presentation of the financial market as a basis for evaluating transformational processes and forecasting its effectiveness through effectiveness is revealed. The main approaches to the classification of the financial market are characterized (by generalized, syncretic, and LOD approaches). The structuring of the financial need based on the convergence of economic relations with the transfer of ownership and the specifics of the legislative regulation of this process is essential and provides the presentation of information in terms of such components as currency market, deposit market, credit market; Securities Market; derivatives market; real estate market. The outlined approach to structuring the financial market forms a conceptual understanding of its model as a system S, which reflects the basic structures necessary to determine the objects of assessment and directions of performance forecasting through performance. To ensure the practical applicability of the conceptual model, modeling procedures, methods and algorithms must be systematically characterized.
Keywords: financial market; transformational forecasting processes; performance